Tata Kelola Sumber Daya Alam Vanili di Kabupaten Sikka - Fransiska Merlina Sareng; Laurensius Petrus Sayrani; Rouwland Alberto Benyamin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to explain the design of vanilla natural resource governance in Sikka Regency, explain the configuration and roles of actors in vanilla natural resource governance in Sikka Regency and explain the implications of vanilla natural resource governance design in Sikka Regency on farmers' welfare. The benefit of this research is as a reference material for the government, entrepreneurs and farmers as actors in vanilla natural resource governance in Sikka Regency in vanilla management. This research uses a qualitative approach with descriptive method with observation, interview and documentation study techniques. The results showed that vanilla governance design in the form of production, distribution and benefits currently implemented in Sikka Regency has not yet obtained optimal results and there are actors who have their respective positions and roles in governance that still need to be coordinated to optimize the benefits of governance. In addition, the design of vanilla governance in Sikka Regency has not been able to improve the welfare of vanilla farmers in Sikka Regency.